Kebijakan Sinergitas R & D Pemerintah, Komunitas Epistemik, dan Sektor Swasta dalam Percepatan Kemandirian Industri Pertahanan - Endro Tri Susdarwono (Jurnal Pemerintahan dan Politik Lokal, 2020)
The purpose of this research is to discuss R&D synergy policies of government, epistemic community, and private sector in accelerating the independence of the Indonesian defense industry. This research is a qualitative research, the type of research uses a comprehensive analytical study and analytical normative approach. The government is aware of the importance of building national research capacity in defense technology. That awareness must be followed up with concrete policies, measurable results, and strategic cooperation with other national components. Human resources or researchers, academics, and innovators who are members of various research institutions are basically a "pool of knowledge" that studies and understands various aspects of the technology, managerial, and social-political industry of the defense, so that it is in an irreplaceable position as the driving force of the ideals of independence in the defense industry. Increasing the capability and mastery of defense industry technology must be done through research and development (R&D) and engineering activities. R&D activities are also an absolute requirement for defense independence and the ability to respond to the development of defense and security technology.